Development of Pop-up Teaching Materials Excretion Systems for Junior High School Students - Nuraini, Zin; Ekaningtias, Maya (DIDAKTIKA : Jurnal Penelitian Tindakan Kelas, 2023)
This study aims to develop pop-up teaching materials for an excretion system material for junior high school students. This research is development research using a 4-D model, which includes four stages: Define, Design, Develop, and Disseminate. Teaching material products are then validated and tested on a limited basis to see the practicality of teaching materials. The pop-up teaching materials developed have met the valid criteria, which have been carried out through media expert validation, content validation, and subject teachers. The validation results show that teaching materials are in the excellent category. In addition, the teaching materials have also fulfilled a series of limited trials on students, indicating that the teaching materials meet practical criteria. In general, the pop-up teaching materials that have been developed are well received by teachers and students. Pop-up teaching materials can increase motivation and student learning outcomes and are suitable for use as science learning materials for junior high school students, especially in excretion system material.